The Participation of Jews Who Are Blind in the Torah Service - Nevins, Daniel S. (Journal of religion, disability & health, 2007)
Jews who are blind are generally obligated to observe the commandments, even those which apparently require vision. They may certainly lead prayer services and chant from the Haftarah for the congregation. Torah reading is a special case since it must be performed directly from a kosher scroll. while adaptive devices may eventually allow a blind person to read directly from the parchment, at this point there are three options for Jews who are blind to read Torah: (1) To receive an aliyah and repeat the words after the sighted reader; (2) to serve as meturgamon, the simultaneous translator of the text (like the Talmudic Rav Yosef, who was blind); (2) chant the maftir section from a braille Bible after it is chanted by a sighted reader as shevii. This responsum was approved by the CJLS on 15, 2003 by a vote of 16 in favor (16-0-0). The responsum includes technical information [Jewish Law] regarding the inclusion of Jews who are blind in the Torah service.